Developing a network time server for LEO optical tracking - Tu Tran Anh; Thuc Nguyen Van; Huy Le Xuan (Bulletin of Electrical Engineering and Informatics, 2022)
In 2021, to enhance the Vietnam's capability in space situational awareness, Vietnam national space center started to develop a space surveillance and tracking system using optical telescopes. An important part of the system is getting accurate timing to guarantee high quality astrometry measurements. A time server was self-developed to meet the demand. The device takes reference time from global navigation satellite system (GNSS) and synchronizes the time to all computers in the network using network time protocol (NTP). GNSS antenna, GNSS receiver module, and Raspberry Pi 4 were used to build a simple stratum 1 NTP time server. The device works smoothly, the synchronization is accurate and stable in both the server and the clients.